How changes in Cu-SSZ-13 catalytic oxidation activity via mild hydrothermal aging influence sulfur poisoning extents - Chen, Yu-Ren; Wei, Lai; Kumar, Ashok; Wang, Di; Epling, William S. (Catalysis science & technology, 2022)
Cu-SSZ-13 is widely used as a NO x reduction catalyst in diesel engine after-treatment systems. However, sulfur, a common although trace component in diesel fuel, can lead to catalyst deactivation. Literature has shown that the relative amounts of Cu sites identified as Z2Cu and ZCuOH under inert conditions lead to different S poisoning extents and those relative Cu site amounts can be influenced by mild hydrothermal aging. Our results confirm this finding, but only for specific conditions, in other words the different Cu distributions leading to different extents of S poisoning is not universally true. Here, we show that the extent of sulfur poisoning by SO 2 in the absence of water is related to SO 2 oxidation on the Cu sites, and more specifically the ZCuOH sites. Therefore, since different pretreatment conditions lead to different relative ZCuOH and Z2Cu distributions, the extent of SO 2 oxidation and therefore S poisoning is influenced by these different pretreatment conditions. The catalyst with more ZCuOH had higher SO 2 oxidation conversions and more deactivation compared to a catalyst with less relative ZCuOH. However, if SO 3 was included during sulfur exposures or if the experiment was performed at relatively low temperature with an SO 2 exposure, changes in the Cu distribution made less or no difference. This is again correlated to S oxidation extents. In the presence of water, the extent of sulfur poisoning is also affected by the catalyst's ability to oxidize SO 2 . And, the presence of water leads to further deactivation than in its absence. The water effect is apparent when the oxidation activity is relatively weak and is less significant when the SO 2 oxidation extent is relatively strong.